Estradiol Treatment Initiated Early After Ovariectomy Regulates Myocardial Gene Expression and Inhibits Diastolic Dysfunction in Female Cynomolgus Monkeys: Potential Roles for Calcium Homeostasis and Extracellular Matrix Remodeling. Issue 21 (6th November 2018) - Michalson, Kristofer T.; Groban, Leanne; Howard, Timothy D.; Shively, Carol A.; Sophonsritsuk, Areepan; Appt, Susan E.; Cline, J. Mark; Clarkson, Thomas B.; Carr, J. Jeffrey; Kitzman, Dalane W.; Register, Thomas C.
Abstract : Background: Left ventricular (LV) diastolic dysfunction often precedes heart failure with preserved ejection fraction, the dominant form of heart failure in postmenopausal women. The objective of this study was to determine the effect of oral estradiol treatment initiated early after ovariectomy on LV function and myocardial gene expression in female cynomolgus macaques. Methods and Results: Monkeys were ovariectomized and randomized to receive placebo (control) or oral estradiol at a human‐equivalent dose of 1 mg/day for 8 months. Monkeys then underwent conventional and tissue Doppler imaging to assess cardiac function, followed by transcriptomic and histomorphometric analyses of LV myocardium. Age, body weight, blood pressure, and heart rate were similar between groups. Echocardiographic mitral early and late inflow velocities, mitral annular velocities, and mitral E deceleration slope were higher in estradiol monkeys (all P <0.05), despite similar estimated LV filling pressure. MCP1 (monocyte chemoattractant protein 1) and LV collagen staining were lower in estradiol animals ( P <0.05). Microarray analysis revealed differential myocardial expression of 40 genes (>1.2‐fold change; false discovery rate, P <0.05) in estradiol animals relative to controls, which implicated pathways associated with better calcium ion homeostasis and muscle contraction and lower extracellular matrix deposition ( P <0.05). Conclusions: Estradiol treatment initiated soon after ovariectomy resulted in enhanced LV diastolic function, and altered myocardial gene expression towards decreased extracellular matrix deposition, improved myocardial contraction, and calcium homeostasis, suggesting that estradiol directly or indirectly modulates the myocardial transcriptome to preserve cardiovascular function.